O papel da acupuntura nos níveis de ansiedade de camundongos submetidos ao labirinto em cruz elevado : implicações com a participação de mecanismos opióides, gabaérgicos e serotoninérgicos - Cole, Eduardo Ferreira (2003)
This work objectified to study the paper of the acupuncture in the leveis of anxiety of mice submitted to the elevated plus-maze (EPM) and its implications with the participation of opioid gabaergic and htergic mechanisms. It was used 170 animais, everybody males, with 12-15 weeks, housed jointly and under conditions of light cycle reverted to the every 12 hours (worked 19 h.), for five weeks you foresaw to the test EPM, thatwas accomplished of 10-14 h., being totally (5 min.) engraving in video for posterior analysis, for trained individual that not the investigator. The mice was separate randomicaly in 13 groups, that submitted the application of EPM 45 min. After the treatments they have been made. The behavior of the animais was evaluated according to the traditional parameters (Lister, 1987) of % n° and % t, submitted to a variance analysis. The groups acupuncture and diazepam accused differences statistic significant of the group control/salina, although, to each other, have not had a comparative posture significant, what drives the conclusion that both groups possess anxiety effect of the same magnitud. The involvement of the opioid system was also verified in the mechanism of action of the acupuncture, because the naloxona totally reverted the anxiety effects of the same.